Oxidative Stress and Antioxidant Treatments in Cardiovascular Diseases - Wenjun Wang; Peter M. Kang (MDPI AG, 2020)
Oxidative stress plays a key role in many physiological and pathological conditions. The intracellular oxidative homeostasis is tightly regulated by the reactive oxygen species production and the intracellular defense mechanisms. Increased oxidative stress could alter lipid, DNA, and protein, resulting in cellular inflammation and programmed cell death. Evidences show that oxidative stress plays an important role in the progression of various cardiovascular diseases, such as atherosclerosis, heart failure, cardiac arrhythmia, and ischemia-reperfusion injury. There are a number of therapeutic options to treat oxidative stress-associated cardiovascular diseases. Well known antioxidants, such as nutritional supplements, as well as more novel antioxidants have been studied. In addition, novel therapeutic strategies using miRNA and nanomedicine are also being developed to treat various cardiovascular diseases. In this article, we provide a detailed description of oxidative stress. Then, we will introduce the relationship between oxidative stress and several cardiovascular diseases. Finally, we will focus on the clinical implications of oxidative stress in cardiovascular diseases.